Hepatitis B surface antigen predicts recurrence after radiofrequency ablation in patients with low hepatitis B virus loads. Issue 52 (December 2017) - Zhang, Lan; Xie, Xiao-Ying; Chen, Yi; Ge, Ning-Ling; Chen, Rong-Xin; Gan, Yu-Hong; Zhang, Bo-Heng; Wang, Yan-Hong; Ren, Zheng-Gang
Abstract : Abstract: Radiofrequency ablation (RFA) is a first-line option for the treatment of small liver cancers, but the recurrence remains a problem affecting long-term survival. Hepatitis B virus (HBV) activity is associated with the prognosis of hepatocellular carcinoma (HCC). We investigated the significance of hepatitis B surface antigen (HBsAg) in HCC recurrence after curative RFA treatment in HBV-related small HCC. We enrolled 404 HBV-related patients with small HCC (⩽3 cm) who underwent curative RFA. We used univariate and multivariate analyses to investigate the baseline levels of HBsAg, in addition to other known risk factors for HCC recurrence, for association with HCC tumor recurrence after curative RFA. The overall 1-, 2-, and 3-year recurrence-free survival (RFS) rates were 75%, 50%, and 34%, respectively. The median recurrence-free time was 25 months. The level of HBsAg was an independent risk factor for recurrence in patients with lower HBV-DNA levels. In hepatitis Be antigen (HBeAg)-negative patients, the 1-, 2-, and 3-year RFS rates were 79%, 64%, and 44%, respectively, for that with low HBsAg levels, compared with 73%, 50%, and 37%, respectively, for that with high HBsAg levels ( P  = .039). HBsAg might serve as a valuable marker to evaluate the risk of HCC recurrence in HBeAg-negative patients with low HBV viral load.